TB_Screen - An Intelligent Tuberculosis Screening System - Mohd Yusoff, Mashor, Prof. Madya Dr.; Teow, Suet Li; Noorhidayah, Abu (Malaysian Invention & Design Society (MINDS), 2010)
Prof. Madya Dr. Mohd Yusoff Mashor and his team won bronze for TB_Screen - An Intelligent Tuberculosis Screening System at 17th International Invention, Innovation & Technology Exhibition (ITEX) 2006, 19th - 21st May 2006 at Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur.